Photoperiod‐independent testicular development in the model newt Pleurodeles waltl. (7th July 2021) - Kyakuno, Mitsuki; Nakamori, Rei; Tazawa, Ichiro; Uemasu, Hitoshi; Namba, Noriyuki; Tsunekawa, Naoki; Noce, Toshiaki; Satoh, Yukio; Takeuchi, Takashi; Hayashi, Toshinori
Abstract: Urodele amphibian newts have unique biological properties in male gametogenesis, in addition to their extreme regenerative capacity. Male newts are able to regenerate new testes even after reaching sexual maturity and can possess multiple testes. Notably, these animals maintain primordial germ cell‐like cells in a tissue adjacent to the testis. Spermatogenesis proceeds while synchronizing in a region‐specific manner in the testis. However, the newt species that have been used most commonly require 2–3 years to achieve sexual maturity, and spermatogenesis in these species shows seasonality. These traits have restricted the use of newts for studies on testicular development and spermatogenesis, and testis development in newts remains poorly characterized. Recently, the Iberian ribbed newt Pleurodeles waltl has been established as an emerging model organism. P. waltl reaches sexual maturity more quick after birth than do other newts and is capable of breeding year‐round. Thus, P. waltl is expected to serve as an appealing experimental model for studying the mechanisms of male gametogenesis in the urodeles. In the present study, we use P. waltl to describe the entire developmental process of the newt testis from primordial gonad to maturity. Notably, the mature testes show synchronized progression of spermatogenesis along the anteroposterior axis. Additionally, we demonstrate that the process of spermatogenesis in P. waltl proceeds irrespective of day length. Our results show that P. waltl newts are a suitable model for investigating the process of testicular development. We also expect that these results will be useful for the maintenance of P. waltl bioresources. Abstract : This study described the developmental process of the testes of a model urodele amphibian newt, P. waltl . Our results demonstrated that spermatogenesis in P. waltl proceeds irrespective of day length.